Novel antiplatelet drugs in clinical development - Ungerer, Martin; Münch, Götz (Thrombosis and Haemostasis, 2013)
The clinical value of antiplatelet compounds strongly depends on the benefit-risk balance between their anti-thrombotic effects and the bleeding risk they incur. This ratio is especially important in the treatment of cerebro-vascular disease. Several novel compounds in clinical development hold promise to improve this benefit-risk ratio.